Fatal systemic morbillivirus infection in bottlenose dolphin, Canary Islands, Spain - Sierra Pulpillo, Eva María; Succa, Daniele; Arbelo Hernández, Manuel Antonio; García Álvarez, Natalia; Andrada Borzollino, Marisa Ana; Déniz Suárez, María Soraya; Fernández Rodríguez, Antonio Jesús (Emerging Infectious Diseases, 2014)
A systemic morbillivirus infection was diagnosed postmortem in a juvenile bottlenose dolphin stranded in the eastern North Atlantic Ocean in 2005. Sequence analysis of a conserved fragment of the morbillivirus phosphoprotein gene indicated that the virus is closely related to dolphin morbillivirus recently reported in striped dolphins in the Mediterranean Sea. 271 269 3,437 6,751 Q1 Q1 SCIE